PERLINDUNGAN HUKUM BAGI TENAGA KEPERAWATAN PADA MASA PANDEMI COVID 19 BERDASARKAN UU TENAGA KESEHATAN NOMOR 36 TAHUN 2014 - Anita Rusmala Dewi (2021)
Article 28D paragraph (1) of the 1945 Constitution states that every person has the right to recognition, guarantee, protection and legal certainty that is just and equal treatment before the law, then Article 57 letter a of Law No. 36 of 2014 concerning Health Personnel also states that health workers in carrying out practices are entitled to obtain legal protection as long as carrying out their duties in accordance with Professional Standards, Professional Service Standards, and Operational Procedure Standards. If you look at the laws and regulations regarding health workers, it seems that there is no one that regulates legal certainty for health workers, especially for nursing personnel, even though there is Law Number 36 of 2014 concerning Health Workers. The problem in this research is whether nursing personnel have received legal protection in carrying out their duties and what are the efforts and steps in legal protection for nursing personnel. This research method uses a normative juridical approach, by examining library materials or secondary data consisting of primary legal materials, secondary legal materials and specific legal materials. Based on the results of the study, nursing staff have received legal protection, but the legal protection measures provided still have weaknesses because some of the rights of health workers have not been fulfilled. In efforts and steps in legal protection for nursing personnel, the government has not been able to provide maximum legal protection and health and safety insurance for nursing personnel due to the Covid 19 pandemic, as mandated by law, in implementing the rights of health workers during the Covid 19 pandemic.